Please don't answer if you don't know the answer!

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

Mar 21st, 2015

To use elimination, we can add the two equations to "eliminate" the x-term:

-2x + 2x +3y - y = 1 + 5

2y = 6

y = 3

Substituting this back into the second equation yields 

2x - 3 = 5

2x = 8

x = 4

So the answer is (4,3).

Mar 21st, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Mar 21st, 2015
...
Mar 21st, 2015
Jun 28th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer